2021
DOI: 10.3389/fbuil.2021.727294
|View full text |Cite
|
Sign up to set email alerts
|

Compound Flooding: Dependence at Sub-daily Scales Between Extreme Storm Surge and Fluvial Flow

Abstract: Estuaries are potentially exposed to compound flooding where weather-driven extreme sea levels can occur synchronously with extreme fluvial discharge to amplify the hazard. The likelihood of compound flooding is difficult to determine due to multiple interacting physical processes operating at sub-daily scales, and poor observation records within estuaries with which to determine potential future probabilistic scenarios. We hypothesize that fluvial extremes can occur within the peak of the surge in small/steep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Further, Paprotny et al (2020) found strong dependencies in surge-precipitation and surge-discharge pairs along the northwestern coasts of Europe. Similar analyses have been conducted on the joint occurrence of storm surge and precipitation across coastal zones of China (Fang et al, 2020), Australia (Wu et al, 2018), storm surge, and river discharge in Britain (Robins et al, 2021), storm surge/sea levels and river discharge over the US coasts (Welch, 2020), among others.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Further, Paprotny et al (2020) found strong dependencies in surge-precipitation and surge-discharge pairs along the northwestern coasts of Europe. Similar analyses have been conducted on the joint occurrence of storm surge and precipitation across coastal zones of China (Fang et al, 2020), Australia (Wu et al, 2018), storm surge, and river discharge in Britain (Robins et al, 2021), storm surge/sea levels and river discharge over the US coasts (Welch, 2020), among others.…”
mentioning
confidence: 77%
“…Previous studies have analyzed compound flood events at global (Eilander et al., 2020; Ward et al., 2018), continental (Ganguli & Merz, 2019; Paprotny et al., 2020), national (Ghanbari et al., 2021; Jalili Pirani & Najafi, 2020), and regional scales (Valle‐Levinson et al., 2020; van Berchum et al., 2020) using statistical and process‐based approaches (Hao et al., 2018). These analyses include characterizing the statistical interrelationships between drivers of flooding based on Bayesian networks (Couasnon et al., 2018; Sebastian et al., 2017), copula theory (Bevacqua et al., 2017; Gori et al., 2020; Moftakhari et al., 2017; Paprotny et al., 2018; Xu et al., 2014), bivariate extreme value distributions (Zheng et al., 2014), correlation and linear regression (Robins et al., 2021), bivariate logistic threshold‐excess model (Zheng et al., 2013) among others. Besides, recent studies have assessed the compound flood impacts and risks through process‐based modeling and hybrid statistical‐dynamical framework (Ganguli et al., 2020; Ganguli & Merz, 2019; Najafi et al., 2021; Wang et al., 2021; Zhang & Najafi, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we limited the time frame of the data sets to the late fall and entire winter season, as storm surges mostly occur in the winter season in northern Europe, see for example (Liu et al, 2022). For the winter season, we used a time frame from December to February, such as also done by Robins et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the effect of compound flooding is more severe on bridges due to the short time period between two or more events. Compound flooding is more frequent during winter/ autumn than summer/spring (Robins et al, 2021). Therefore, engineers must be able to design the bridges to withstand the forces of pre-evaluated shock sizes and consider urban planning by identifying areas that are at risk of flooding, and then developing strategies to reduce the risk of flooding in those areas.…”
mentioning
confidence: 99%